Attention deficit hyperactivity disorder, tic disorder, and allergy: is there a link? A nationwide population‐based study. (12th November 2012) - Chen, Mu‐Hong; Su, Tung‐Ping; Chen, Ying‐Sheue; Hsu, Ju‐Wei; Huang, Kai‐Lin; Chang, Wen‐Han; Bai, Ya‐Mei
<x xml:space="preserve">Abstract</x> Background: Attention deficit hyperactivity disorder (ADHD) and tic disorder usually co‐occur in the same individuals, but the underlying mechanisms remain unclear. Previous evidence has shown that a frequent coexistence of allergic diseases was noted in patients with ADHD or tic disorder. We attempted to investigate the possible link among ADHD, tic disorder, and various allergic diseases. Methods: Utilizing the Taiwan National Health Insurance Research Database from 1996 to 2010, 5, 811 patients with ADHD alone, 1, 816 patients with tic disorder alone, and 349 patients with dual diagnoses of ADHD and tic disorder were identified and compared with age‐/gender‐matched controls (1:4) in an investigation of the association among ADHD, tic disorder, and allergic diseases. Results: Patients with dual diagnoses of ADHD and tic disorder had a significantly higher prevalence of allergic diseases and psychiatric comorbidities, including allergic rhinitis (43% vs. 28.4% vs. 33.6% vs. 19.7%, p < 0.001), asthma (27.5% vs. 17.2% vs. 18.2% vs. 11.9%, p < 0.001), atopic dermatitis (10.6% vs. 8.4% vs. 7.0 vs. 5.9%, p < 0.001), allergic conjunctivitis (55.6% vs. 34.7% vs. 43.5% vs. 26.3%, p < 0.001), obsessive compulsive disorder (4.0% vs. 1.3% vs. 2.0% vs. 0.1%, p < 0.001), and anxiety disorder (22.1% vs. 18.0% vs. 6.0% vs. 0.5%, p < 0.001) than the ADHD alone group, the tic alone group, and the control group. Furthermore, ADHD patients with more allergic diseases (≥3 comorbidities: OR: 3.73, 95% CI: 2.65∼5.25; 2 comorbidities: OR: 2.52, 95% CI: 1.82∼3.47; 1 comorbidity: OR: 1.87, 95% CI: 1.41∼2.49) exhibited an increased risk of tic disorder compared with ADHD patients without allergic disease. Conclusion: A significant association among ADHD, tic disorder, and allergic diseases was noted in our study. The results may inspire further studies to clarify the underlying mechanisms and help us understand more about the complex etiology of ADHD, tic disorder, and their co‐occurrence.